7T Proton Magnetic Resonance Spectroscopy of the Anterior Cingulate Cortex in First-Episode Schizophrenia. (29th January 2018) - Reid, Meredith A; Salibi, Nouha; White, David M; Gawne, Timothy J; Denney, Thomas S; Lahti, Adrienne C
Abstract: Recent magnetic resonance spectroscopy (MRS) studies suggest that abnormalities of the glutamatergic system in schizophrenia may be dependent on illness stage, medication status, and symptomatology. Glutamatergic metabolites appear to be elevated in the prodromal and early stages of schizophrenia but unchanged or reduced below normal in chronic, medicated patients. However, few of these studies have measured metabolites with high-field 7T MR scanners, which offer higher signal-to-noise ratio and better spectral resolution than 3T scanners and facilitate separation of glutamate and glutamine into distinct signals. In this study, we examined glutamate and other metabolites in the dorsal anterior cingulate cortex (ACC) of first-episode schizophrenia patients. Glutamate and N -acetylaspartate (NAA) were significantly lower in schizophrenia patients vs controls. No differences were observed in levels of glutamine, GABA, or other metabolites. In schizophrenia patients but not controls, GABA was negatively correlated with the total score on the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) as well as the immediate memory and language subscales. Our findings suggest that glutamate and NAA reductions in the ACC may be present early in the illness, but additional large-scale studies are needed to confirm these results as well as longitudinal studies to determine the effect of illness progression and treatment. The correlation between GABA and cognitive function suggests that MRS may be an important technique for investigating the neurobiology underlying cognitive deficits in schizophrenia.